2022
DOI: 10.3389/fendo.2022.955250
|View full text |Cite
|
Sign up to set email alerts
|

Individualized model for predicting pathological complete response to neoadjuvant chemotherapy in patients with breast cancer: A multicenter study

Abstract: BackgroundPathological complete response (pCR) is considered a surrogate for favorable survival in breast cancer (BC) patients treated with neoadjuvant chemotherapy (NACT), which is the goal of NACT. This study aimed to develop and validate a nomogram for predicting the pCR probability of BC patients after NACT based on the clinicopathological features.MethodsA retrospective analysis of 527 BC patients treated with NACT between January 2018 and December 2021 from two institutions was conducted. Univariate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The nomogram is a simple and effective tool for predicting the outcome [20]. The nomogram prediction model established based on the results of regression analysis can predict the pathological response of tumor patients after NAC [21][22][23][24], and the prediction ability of these models is pretty good. Multivariate regression analysis in our study showed that PLR, PLT, WBC and tumor grade were independent predictive factors of pCR.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
“…The nomogram is a simple and effective tool for predicting the outcome [20]. The nomogram prediction model established based on the results of regression analysis can predict the pathological response of tumor patients after NAC [21][22][23][24], and the prediction ability of these models is pretty good. Multivariate regression analysis in our study showed that PLR, PLT, WBC and tumor grade were independent predictive factors of pCR.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
“…This is in keeping with several other studies. Qian et al found lower T scores and smaller tumor size correlated with higher pCR rates [51]. Goorts et al reported lower T stages had signi cantly higher pCR [53].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor biology consistently emerges as a factor linked to pCR in multiple studies [50,51]. Previously reported racial disparities in survival may be due to additional factors which are potentially inter-related and would therefore be di cult to isolate from one another, such as socioeconomic differences, differences in insurance, and differences in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, based on the imaging, Li et al [ 56 ] built an imaging model with diffusion-weighted MRI in neoadjuvant immunotherapy, with an AUC of 0.73 for predicting pCR. One recent study developed a prediction model with an AUC of 0.825 based on age, AJCC T stage, Ki67, HER2, and hormone receptor status [ 57 ]. However, this study had a relatively small sample size (n = 527).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to prior studies [ 24 , 55 , 57 ], the ER, PR, Ki67, and p53 thresholds were established based on ROC analysis rather than simply categorizing them as positive or negative. In order to facilitate clinical application, we created a user-friendly nomogram based on our Cox model.…”
Section: Strengths and Limitationsmentioning
confidence: 99%